Modelling study of vanadium based alloys and crystalline porous materials for gas separation membranes - Borisova Evtimova, Jenny; De Luca, Giorgio; Curcio, Efrem; Molinari, Raffaele (My University, 2016)
Gas! membrane! separation! is! an! attractive! technology! that! is! often! superior! to! other! more! conventional! procedures! for! separation! of! gaseous! species! in! terms! of! energy! consumption! and! environmental! impact.! A! key! factor! for! membrane! separations! is! the! membrane! itself! with! its! properties,! which! determine! the! overall! performance! of! the! process.! One! essential! membrane! characteristic!is!the!transport!selectivity.!High!separation!factors!are!especially!difficult!to!achieve! for! mixtures! of! light! gases! having! comparable! kinetic! diameters.! Moreover,! high! permeability,! correspondingly! high! solubility! and! diffusivity! in! dense!membranes,! are! crucial! aspects! for! the! performance! and! further! practical! application! of!membrane! devices.! In! this! frame,! the!material! used!as!a!selective!layer!is!determinant.!Therefore,!scientists!devote!immense!efforts!to!the!search! of! optimal! gasBsorbent! combinations,! including! thorough! study! of! existing! structures! and! elaboration!of!new!ones!with!sieving!properties.!The!large!effort!and!time!required!for!preparation! and!experimental!testing!of!materials!impede!the!advancement!of!new!membranes.! In!this!study,!we!propose!procedures!based!on!computational!calculations!and!theoretical!models! that! can!be!used! to!predict! the!behaviour!of! some!of! the!membrane!materials!of! interest! for! gas! separation! applications.! In! particular,! we! focus! on:! i)! bodyBcentred! cubic! VNiTi! alloys! as! novel! materials!for!H2Bselective!dense!membranes!and!ii)!crystalline!porous!materials!that!are!attractive! media!for!separation!of!light!gases!such!as!H2,!O2,!CO,!CO2,!CH4!and!N2.!These!two!types!of!materials! are! treated! using! different! methodologies,! adapted! to! the! needs! of! our! research! objectives! associated!to!each!material.! In!the!case!of!dense!metal!membranes,!the!long!standingBcontroversy!over!occupancy!of!interstitial! hydrogen! in! VBbased! alloys! is! addressed.! The! VBNiBTi! system! is! of! particular! interest! here,! exhibiting!high!H2!permeability!and!improved!mechanical!properties!relative!to!pure!V.!This!work! intends!to!gain!understanding!of!hydrogenBmetal!interactions!as!function!of!alloy!composition!and! thereby!to!optimize!these!new!materials!and!advance!their!development!as!novel!membranes!for! H2! separation.!We! use! a! firstBprinciples! approach! that! gives! insights! into! the! sites! preference! of! hydrogen! and! assesses! the! role! of! Ti! and! Ni! substitutional! solutes! for! the! hydrogen! absorption! affinity.! The!method! based! on!Density! Functional! Theory! requires! no! experimental! input! except! crystal!structure!information.!Furthermore,!it!uses!no!empirical!or!fitting!parameters!in!contrast!to! other!computational!techniques.!Hence!this!approach!provides!an!alternative!way!to!explore!new! metal!alloys!for!H2!separation!membranes.!The!applied!methodology!can!be!used!further!in!highB throughput!calculations!to!screen!various! alloy!compositions.!The!heretoBreported!results!will!be! used!as!guidance!for!tailoring!the!formulation!of!VNiTi!solid!solutions!and!preparation!of!low!cost†! dense!alloy!membranes!in!the!frame!of!other!projects!(e.g.!European!DEMCAMER!project).! Further,! we! explore! how! singleBcomponent! inputs! can! be! used! to! forecast! the! ideal! selectivity! towards! light! gases! of! crystalline! porous!materials,! used! for!membrane! preparation.! Theoretical! models! for! describing! gas! separation! properties! of! zeotype! materials! as! function! of! structural! characteristics!and!operation!conditions!are!proposed.!The!model!parameters!can!be!obtained!as! experimentally!as!well!as!computationally.!To!analyse!the!extent!of!validity!and!limitations!of!the! models,!ideal!selectivities!of!few!crystalline!porous!materials!are!evaluated,!including!widely!used! zeolites!(NaA,!CaA)!and!a!metal!organic!framework!structure!(ZIFB8).!The!results!verified!that!the! theoretical!expressions!could!be!used!for!screening!series!of!zeotype!materials!when!reliable!single! gas!adsorption!data!are!available.!However,!since!the!models!don’t!take!into!account!all!parameters! (namely! related! to! the! membrane! design)! and! mechanisms! involved! in! gas! transport! through! porous!membranes,!their!predictions!should!be!considered!as!values!referring!to!an!ideal!case.!
Scuola di Dottorato "Pitagora" in Scienze Ingegneristiche, Dottorato di Ricerca in Ingegneria Chimica e dei Materiali, Ciclo XXVIII, a.a. 2015-2016
Keywords: Ingegneria chimica; Leghe metalliche; Zeoliti